Indonesian Tourism Diplomacy to India - Anton Minardi; Taufik Taufik; Rini Afriantari; Neneng Uswatun Hasanah (Lasigo Akademia Indonesia, 2020)
Nowadays, tourism is one of the sectors that have a significant influence on the development of a country in various fields, including in the economic area and also diplomatic relations among the nations. The tourism sector is the fourth largest foreign exchange earner for Indonesia in 2015. Indonesia, with all its natural wealth and cultural heritage, continually striving to develop the tourism sector through the Ministry of Tourism Indonesia. Indonesia Ministry of Tourism is conducting tourism diplomacy by holding promotions to various countries that have the potential to attract tourists to Indonesia, one of them is India. This article seeks to analyze how Indonesia’s diplomacy to attract peoples from India whereas as rapidly developed country in the world. This study used a literature review to analyze Indonesian tourism diplomacy to India. The findings show that through tourism diplomacy, we find that Indonesian attracted India by utilized cultural similarities, has been succeed in increasing tourists' visits from India.